Impact of bulk density estimation in mine planning. Issue 1 (2nd January 2021) - Reis, Celso; Arroyo, Carlos; Curi, Adilson; Zangrandi, Marcelo
ABSTRACT: The incorporation of bulk density uncertainty for Mineral Resource and Mineral Reserves (MRMR) steps is of great importance for successful mine planning process. In practice, most mining projects use an average density value for each lithological type of the deposit. However, density determinations require special attention as they directly affect the conversion of volumes to tonnages and ore grades to metal contents. The objective of this study is to measure and minimize the risks associated with the MRMR stages, including the density variability in mine planning. Traditional interpolation techniques in geostatistics were used to represent density spatial distribution in a block model, similarly to those used for grade estimation. This approach was developed and applied at a Brazilian iron ore mine. The results indicate MRMR are underestimated if density uncertainty is not considered. Mine design changes were observed, including 5% impact on the Life-of-mine (LOM) and 2% in Net Present Value (NPV).